A Novel Compact, Broadband, High Gain Millimeter-Wave Antenna for 5G Beam Steering Applications - ÖZPINAR, HÜRREM; AKŞİMŞEK, HÜSEYİN SİNAN; Tokan, Nurhan Türker (IEEE Institute of Electrical and Electronics Engineers, Inc., 2020)
The millimeter-wave (mmWave) antennas for smartphones are one of the key components to complete the transition to 5G mobile networks. Although research and development of mmWave 5G antennas for cellular handsets are currently at the center of a significant research effort in both academia and telecommunication industry, a systematic antenna design approved by wireless community has not been proposed yet. With this communication, we propose a novel, high gain, wide band and compact mmWave 5G antenna, namely clover antenna for cellular handsets. The presented antenna has clover like conductor profile whose parameters can be adjusted to obtain high gain or wide band. The designed antennas are simulated with a widely used full-wave analysis tool. Numerical results of the mmWave antenna are confirmed successfully by the experimental results in ${{\text{24}}}$-${\text{28}}$ GHz band. The antenna achieves measured peak gain of ${\text{ 7.8}}$-${\text{9}}$ dBi in the band. Besides, with a ${\text{16}}$-element clover antenna array, the beam steering capability of the antenna is demonstrated. Beam steering between ${{ \pm \text{45}<^>\circ }}$ is achieved with low side lobe levels. Practical design considerations for the integration of the arrays in handset to obtain full-coverage in horizontal plane are investigated. The calculated spatial peak power density values of the proposed array on the outer surface of a head phantom are demonstrated for different scan angles.
Keywords: 5G; Beam Steering; Cellular; Electromagnetic Field Exposure; Millimeter-Wave (mmWave); Phased-Array